U-Prove Collaborative Issuance Extension - Paquin, Christian; Zaverucha, Greg (Microsoft Research, 2014)
This document extends the U-Prove Cryptographic Specification by specifying how the Prover and the Issuer can collaborate to issue tokens encoding attributes unknown to the Issuer.